(untitled) (Colombia Medica, 1986)
A study carried out in 1974 in the state of Valle del Cauca showed that both surgeons and operating rooms were underutilized according to the population’s needs for surgical care. Low productivity of the surgeons and low coverage were also common features. Since 1974, there have been important changes in surgical care in Cali. This paper analyzed the 1615 surgeries performed in six governmental institutions during February 1985 and compared them with the findings in the 1974 survey to measure the effect of those changes.